Efficient Adsorptive Separation and Determination of Phenolic Acids from Orange Peels Using Hyper-Crosslinked Polymer Based Zeolitic Imidazolate Framework-8 (ZIF-8) Composites. (1st November 2020) - Sun, Liping; Tang, Weiyang; Zhu, Tao; Row, Kyung Ho
Abstract: A new and efficient hypercrosslinked polymer-based zeolitic imidazolate framework-8 composite called ZIF-8-HCP was synthesized. The properties of the material including zeolitic imidazolate framework-8 and hypercrosslinked polymer were analyzed using seven characterization methods. In addition, the materials were used as adsorbents for the dispersion solid-phase extraction for the separation and determination of phenolic acids in orange peel samples. The adsorption capacities of the resulting materials were characterized. The selectivity of zeolitic imidazolate framework-8 was greatly enhanced after the introduction of a hyper-crosslinked polymer as the skeleton. The microstructure modification introduced a large number of mesoporous sites that allowed better adsorption of the caffeic acid and ferulic acid targets. The adsorption capacities of the composite ZIF-8-HCP were 31.72 mg/g for the former and 15.58 mg/g for the latter. In addition, the limits of detection and quantification were 0.0188 and 0.0627 μg/mL and 0.0177 and 0.0592 μg/mL, respectively. A feasible analytical method was established for the targets in orange peel samples using the ZIF-8-HCP with satisfactory extraction recoveries of 92.90% and 98.87%. The proposed method using the synthesized material was employed to the trace determination of the phenolic acids by high-performance liquid chromatography (HPLC).